Altered neurometabolite development in HIV-infected children: correlation with neuropsychological tests. - Keller, M A; Venkatraman, T N; Thomas, A; Deveikis, A; LoPresti, C; Hayes, J; Berman, N; Walot, I; Padilla, S; Johnston-Jones, J; Ernst, T; Chang, L (Neurology)
Background: HIV-infected children have abnormal cerebral metabolites, measured by proton MR spectroscopy ((1)H-MRS), but how these abnormalities relate to brain function is unclear.Methods: Metabolite concentrations in five brain regions of 20 HIV-infected and 13 control children were measured, and these findings were correlated with age, log(10) plasma viral load, CD4 count, and neuropsychological scores.Results: Compared with control subjects, HIV patients had decreased choline concentration [Cho] in left frontal white matter (LFW) (-12%; p = 0.04); those with high viral load (>5,000 HIV RNA copies/mL) had decreased right basal ganglia (RBG) [Cho] (-15%; p = 0.005), and [Cr] (-13%; p = 0.02). Patients with high viral load also had higher [Cho] in the midfrontal gray matter (MFG) (+25%; p = 0.002) and lower myo-inositol [Ins] in the RBG (-18%; p = 0.04) than patients with low HIV viral load. N-Acetyl aspartate concentration ([NAA]) correlated with age in right frontal white matter (RFW) (r = 0.59, p = 0.04), LFW (r = 0.66, p = 0.02), and right hippocampus (RHIP) (r = 0.69, p = 0.02) only in control subjects. In contrast, [Ins] correlated with age in both RFW and LFW (r = 0.71, p = 0.0006; r = 0.65, p = 0.006) only in the HIV patients. Log(10) plasma viral load correlated positively with [Ins] in RFW (r = 0.54, p = 0.02) and [Cho] in MFG (r = 0.49, p = 0.04). Compared with control subjects, HIV patients had poorer spatial memory (p = 0.045) and delayed spatial memory correlated with [Cho] in RHIP (r = 0.68, p = 0.02).Conclusions: These data suggest that normal brain development may be affected in children infected with HIV at birth, particularly evidenced by the lack of age-related increases in the neuronal marker [NAA]. Early, aggressive treatment of infants with HIV before development of encephalopathy is warranted.